Proceso de Investigación/Diagnóstica y Elaboración del Informe Social - Maravilla Sandoval, Dayana Alejandra; Rivas Muñoz, Sara Beatriz (Universidad de El Salvador.Facultad de Ciencia y Humanidades, 2025)
Disponible en soporte impreso